The Sensory Gatekeeper of the Larynx: Anatomy and Clinical Importance of the Internal Branch of the Superior Laryngeal Nerve - Alexandra Diana Vrapciu; Iulian Brezean; Răzvan Costin Tudose; Mugurel Constantin Rusu; George Triantafyllou; Maria Piagkou (Diagnostics)
The internal branch of the superior laryngeal nerve (IbSLN) plays a critical role in the sensory innervation of the supraglottic larynx. It is essential for protective reflexes such as coughing and swallowing. This nerve is frequently at risk during surgeries involving the cervical region, including thyroidectomy, carotid endarterectomy, and anterior cervical spine procedures. Injury to the IbSLN may lead to postoperative complications. A comprehensive review of the morphological and topographic characteristics of the IbSLN is presented, focusing on its anatomical course, relationships with key vascular structures, branching patterns, and clinically significant variations.